Fabrication and mechanical properties of Al2O3–TiC ceramic composites synergistically reinforced with multi-walled carbon nanotubes and graphene nanoplates. Issue 12 (15th August 2020) - Sun, Daming; Jiang, Xiaosong; Su, Lili; Sun, Hongliang; Hu, Chunfeng; Song, Tingfeng; Luo, Zhiping
Abstract: In this study, Al2 O3 –TiC composites synergistically reinforced with multi-walled carbon nanotubes (MWCNTs) and graphene nanoplates (GNPs) were prepared via spark plasma sintering (SPS). The effects of the MWCNT and GNP contents on the phase composition, mechanical properties, fracture mode, and toughening mechanism of the composites were systematically investigated. The experimental results indicated that the composite grains became more refined with the addition of MWCNTs and GNPs. The nanocomposites presented high compactness and excellent mechanical properties. The composite with 0.8 wt% MWCNTs and 0.2 wt% GNPs presented the best properties of all analysed specimens, and its relative density, hardness, and fracture toughness were 97.3%, 18.38 ± 0.6 GPa, and 9.40 ± 1.6 MPa m 1/2, respectively. The crack deflection, bridging, branching, and drawing effects of MWCNTs and GNPs were the main toughening mechanisms of Al2 O3 –TiC composites synergistically reinforced with MWCNTs and GNPs.